Expression of AMT1;1 and AMT2;1 is stimulated by mineral nitrogen and reproductive growth stage in barley under field conditions. (21st April 2023) - Esmaeilzadeh-Salestani, Keyvan; Samandari_Bahraseman, Mohammad Rasoul; Tohidfar, Masoud; Khaleghdoust, Banafsheh; Keres, Indrek; Mõttus, Aleks; Loit, Evelin
Abstract: Barley ( Hordeum vulgare ) is an important cereal for providing food and feed. Nitrogen (N) is a crucial element for plant productivity. N fertilizing management requires large amount of money and energy, and excess application makes environmental hazards. Therefore, the future varieties and management systems need to be more efficient in nitrogen uptake and utilization. Ammonium transporters (AMTs) are important genes in N uptake and transport. Since N has strong impact on biomass production, it was hypothesized that N rate and barley growth stage have significant influence on AMT expression under field conditions. The field experiment was carried out in 2019 to determine expression patterns of Hv AMT1;1 and Hv AMT2;1 genes at different growth stages under different N fertilizer rates and types. A down-regulation of Hv AMT1;1 and Hv AMT2;1 until heading and up-regulation at anthesis stage was observed compared to the unfertilized treatment, mineral fertilizers having stronger effect. Hv AMT1;1 was expressed 2.8 times more than Hv AMT2;1 at the same time. There was a positive correlation between both AMT genes expression and N content in leaves at anthesis as well as 1000-kernel weight. In conclusion, nitrogen uptake and translocation is partially governed by Hv AMT1;1 and Hv AMT2;1, and it is a valuable candidate for breeding programs.